Bacterial XylRs and synthetic promoters function as genetically encoded xylose biosensors in Saccharomyces cerevisiae - Teo, Wei Suong (2015)
Lignocellulosic biomass is a sustainable and abundant starting material for biofuel production. However, lignocellulosic hydrolysates contain not only glucose, but also other sugars including xylose which cannot be metabolized by the industrial workhorse Saccharomyces cerevisiae. Hence, engineering of xylose assimilating S. cerevisiae has been much studied, including strain optimization strategies. In this work, we constructed genetically encoded xylose biosensors that can control protein expression upon detection of xylose sugars. These were constructed with the constitutive expression of heterologous XylR repressors, which function as protein sensors, and cloning of synthetic promoters with XylR operator sites. Three XylR variants and the corresponding synthetic promoters were used: XylR from Tetragenococcus halophile, Clostridium difficile, and Lactobacillus pentosus. To optimize the biosensor, two promoters with different strengths were used to express the XylR proteins. The ability of XylR to repress yEGFP expression from the synthetic promoters was demonstrated. Furthermore, xylose sugars added exogenously to the cells were shown to regulate gene expression. We envision that the xylose biosensors can be used as a tool to engineer and optimize yeast that efficiently utilizes xylose as carbon source for growth and biofuel production.